Pengaruh Kompetensi Pegawai Dan Lingkungan Kerja Terhadap Kualitas Layanan Pegawai UPTD Puskesmas Natar Kecamatan Natar Kabupaten Lampung Selatan - Septina, Nita; Josiah , Trisnowati (Utami Publisher, 2025)
This study aims to analyze the impact of employee competence and work environment on the quality of services at UPTD Puskesmas Natar, Natar District, South Lampung Regency. The background of this research is based on the importance of puskesmas as a basic health facility that provides comprehensive, integrated, equitable, acceptable, and affordable health efforts for the community, in accordance with Permenkes No. 43 of 2019. UPTD Puskesmas Natar faces various challenges in enhancing the competence of medical personnel, creating a conducive work environment, and maintaining the quality of health services.Service quality is the extent to which the services provided by an organization meet or exceed customer expectations. To ensure consistent service quality, it is essential to identify the factors affecting service quality, including employee competence and the work environment. The method used in this study is a questionnaire. The sample size of this study is 44 respondents. Statistical tests were conducted using multiple linear regression.Based on the research results, it is found that employee competence and work environment individually or jointly influence the service quality at UPTD Puskesmas Natar. This is evidenced by the employee competence variable (X1) affecting service quality (Y) by 68.1%. The work environment variable (X2) affects service quality (Y) by 66.1%. The employee competence variable (X1) and the work environment variable (X2) jointly affect service quality (Y) by 85.3%. This means that an increase in employee competence and the work environment will lead to an increase in service quality, and vice versa. Therefore, in order to improve service quality, it is necessary to consider the contributions of employee competence and the work environment.